The White Dwarf Mass versus X-Ray Temperature Relationship of Dwarf Novae, Revisited - Mukai, Koji; Byckling, Kristiina (Research notes of the AAS, 2022)
Most methods used to determine the white dwarf mass in non-magnetic cataclysmic variables are subject to large systematic errors. X-ray spectroscopy has the potential to enable mass estimation with a good accuracy, when calibrated against accurate and reliable values. This is now possible thanks to the work of Pala et al., who estimated the white dwarf masses for 43 cataclysmic variables relying in part on Gaia distances. In this research note we provide a brief update on the X-ray temperature versus white dwarf mass relationship using the X-ray spectroscopy results of Byckling et al. compared against the results of Pala et al., thereby putting the X-ray spectroscopy method on a securer footing.